Uso de los curso online masivo abierto para mejorar el aprendizaje de los estudiantes del 1º de bachillerato de la Unidad Educativa Diez de Agosto, ubicada en el Cantón Montalvo, Provincia de los Ríos periodo lectivo 2016-2017. - Bonilla Contreras, Pamela Katherine (2016)
The following final research report aims at the application of a MOOC for the Subject of Informatics Applied to Education as a learning strategy in the students of the First of Bachillerato of the Educational Unit Diez de Agosto of Canton "Montalvo", Province "Los Rivers "in the Lecture Period 2016-2017. Nowadays they are exploring new forms of education as such the MOOC were born of that need, they have taken an innovative role of education trying to eliminate traditionalism in institutions but what is important is student learning, so that is The primary objective of the MOOCs. But for this to be given one needs the motivation and dedication of the students as it is of paramount importance.